Group formation using genetic algorithm - Che Ani, Zhamri; Husin, Mohd Zabidin; Yasin, Azman (Universiti Utara Malaysia, 2009)
Due to the increasing of complexity in software projects, group work is becoming more important in order to ensure quality software products can be delivered on time.Thus, in universities, group work is seen as a good preparation for students to industry because by working in group, it can reduce the individual workload,improve the ability to manage a project and enhance the problem solving skills. However, due to lack of programming skills especially in Java programming language and the inability to have meetings frequently among the group members,most of the students’ software project cannot be delivered successfully.To solve this problem, systematic group formation is one of the initial factors that should be considered to ensure that every group consists of quality individuals who are good in Java programming and also to ensure that every group member in a group are staying closer to each other.In this research, we propose a method for group formation using Genetic Algorithms, where the members for each group will be generated based on the students’ programming skill and location of residential colleges.